Reading practices in a public library in Lima: the case of frequent child readers - Sandoval Figueroa, Carmen María (2019)
This article shows the results of research carried out on a public library locatedin Lima where we observed the reading practices of children who were frequentusers of the reading rooms during the months of August to December of 2016. The results indicate that the children develop their own reading practices because of the frequent use of the room, the participation of the literacy mediator, and their role as dynamic agents in the use of the library. The reading practices have components: a playful aspect, an educational aspect and a functional aspect. As the child becomes a reader, reading  practices become increasingly complex and acquire other characteristics. Reading practices allow children who are frequent users of the library to, in time, acquire the role of literacy mediators.